Peran Industri Ritel Bagi Pertumbuhan Ekonomi Nasional - Sudarma, Ade (PT. Alahyan Publisher Sukabumi, 2023)
The webinar on the role of the retail industry in national economic growth is one solution to the problems faced by the retail industry and the wider community, namely the lack of strategies implemented by the retail industry to increase economic resilience during the pandemic. The purpose of this activity is to increase understanding of the role of the retail industry in economic growth. The method of implementing this activity is webinars for students, the retail industry, high school students in Sukabumi City, and the general public. Partners in this webinar activity are the retail management study program, the Dikumindag of Sukabumi City, and the Cooperatives and SMEs Office of Sukabumi Regency. The evaluation was carried out by giving questionnaires to webinar participants before and after delivering the material, and the result was that participants' comprehension ability increased by 38.14%.